M1/M2 Macrophage Skewing is Related to Reduction in Types I, V, and VI Collagens with Aging in Sun-Exposed Human Skin - Satoshi Horiba; Munetaka Kawamoto; Ryozo Tobita; Ryota Kami; Yuki Ogura; Junichi Hosoi (JID Innovations, 2023)
Sun-exposed, aged human skin is fragile because of collagen fragmentation and loss. We recently reported that the balance of M1 and M2 macrophages is associated with chronic inflammation and related inflammaging in sun-exposed human skin. In this study, we analyzed its role in the maintenance of collagen matrix formation by performing histological analyses of human facial skin. In addition, RNA sequencing, protein assays, and functional assays revealed the details of the mechanism. The number of M2 macrophages was positively correlated with the abundance of type I collagen, whereas the M1/M2 ratio was negatively correlated with the abundance of type V and VI collagen, which are the essential minor collagens required for collagen assembly in the skin; however, there was no correlation with type III collagen. Furthermore, M2 macrophages induced the expression of the proteins required for the assembly of collagen fibrils, suggesting that the M1/M2 balance controls not only the quantity but also the quality of the collagen matrix. Indeed, M1 macrophages induced abnormal collagen fibrils consisting of types I, V, and VI collagens. Our results demonstrate the relationship between the M1/M2 balance and the dysregulation of collagen homeostasis in photoaged skin and suggest the possible involvement of macrophages in skin photoaging.